PERAN KOMUNITAS NGEJAH DALAM MENSUKSESKAN PROGRAM LITERASI MELALUI TAMAN BACA MASYARAKAT AIUEO - Wiwin Herwina; Dede Nurul Qomariah; Faisal Sulistio (IKIP Siliwangi Bandung, 2021)
This study aims to determine the role of the ngejah community in the successed of the literacy program through TBM AIUEO. Descriptive research method with a qualitative approach is used in this study. Data collection techniques were carried out through field observations, interviews and documentation studies. Data analysis was performed by reducing data, presenting data, and drawing conclusions. The results showed that: a) the role of the ngejah community in the successed of the literacy program, namely as a mobilizing community in society. The colonial community as one of the providers of education services through literacy programs is carried out programmatically, according to the needs of the community. This is evidenced in the implementation of a well-planned literacy program starting from the planning, organizing, implementing to evaluation stages; b) literacy programs can be successful if they are supported by adequate resources to achieve program objectives. Reading materials, reading numbers, reading frequency, the level of active community participation, and the impact of the program are proven to support the role of the ngejah community in the success of the literacy program implemented at TBM AIUEO.Penelitian ini bertujuan untuk mengetahui peran komunitas ngejah dalam menyukseskan program literasi melalui TBM AIUEO. Metode penelitian deskriptif dengan pendekatan kualitatif digunakan dalam penelitian ini. Teknik pengumpulan data dilakukan melalui observasi lapangan, wawancara dan studi dokumentasi. Analisis data dilakukan dengan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: a) peran komunitas ngejah dalam mensukseskan program literasi yakni sebagai komunitas penggerak di masyarakat. Komunitas ngejah sebagai salah satu penyedia layanan pendidikan melalui program literasi dilakukan secara terprogram, sesuai dengan kebutuhan masyarakat. Hal ini dibuktikan dalam pelaksanaan program literasi yang terencana dengan baik mulai dari tahapan perencanaan, pengorganisasian, pelaksanaan hingga evaluasi; b) program literasi dapat berhasil apabila didukung dengan sumber daya yang memadai guna mencapai tujuan program. Bahan bacaan, jumlah bacaan, frekuensi membaca, tingkat partisipasi aktif masyarakat, dan dampak program terbukti dapat mendukung peran komunitas ngejah dalam mensukseskan program literasi yang dilaksanakan di TBM AIUEO.